ENTREPRENEURIAL RESILIENCE VARIABLE: INFLUENCED BY MENTORING, CULTURAL BACKGROUND AND PROFIT - Hanny, Rissa; Husen, Achmad; Suparno, Suparno (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to analyze the influence of mentoring, cultural background, and profit on the entrepreneurial resilience of student entrepreneurs at the Entrepreneurship Laboratory (LabStore) of Pamulang University in South Tangerang, Banten. The research also examines the direct and indirect relationships between these variables in enhancing the entrepreneurial resilience of student entrepreneurs. The methodology used is a quantitative survey with a multiple linear regression approach. The research sample consists of 120 respondents selected using probability sampling techniques. Data was collected using a questionnaire based on a Likert scale, which has been evaluated for both validity and reliability. The study results show that mentoring, cultural background and profit significantly affect the entrepreneurial resilience of student entrepreneurs, both simultaneously and partially. The F-test indicates that the regression model meets the model fit criteria, and simultaneously, the dependent variable is influenced by the three independent variables.Keyword: Entrepreneurial Resilience, Mentoring